Muddied Waters : Race, Region, and Local History in Colombia, 1846-1948 - Appelbaum, Nancy P. (Book collections on Project MUSE., 2003)
Claims that Colombia's present-day regional and local hierarchies were shaped by 19th and 20th century processes of colonization and that regionalism and race are tied into Colombia's history of violence.